Green biofuels and bioproducts: bases for sustainability analysis. Issue 5 (17th July 2017) - Ramos, Juan L.; García‐Lorente, Francisco; Valdivia, Miguel; Duque, Estrella
Abstract : Currently the chemical industry is largely petroleum based and although the number of ongoing large‐scale biocatalytic processes are relatively low, a trend in growth is expected and the Organization for Economic Co‐operation and Development (OECD) and other agencies aim to have 30% of the total chemical industry based on renewable sources by 2050 (Philp et al ., 2013). At present a good number of bio‐based products (bioethanol, acids such as lactic, succinic, itaconic and others) are derived from corn syrup and other sugar sources (Geiser et al ., 2016; Ramos et al ., 2016a); however, because of the food v fuel controversy new trends have been directed towards the production of bioproducts/biofuels from lignocellulosic biomass—the most abundant and important renewable source for alternative petrol derivatives. We discuss here the bases for sustainable bioenergy production.